EFEKTIVITAS PEMBELAJARAN BAHASA ARAB SISWA (kelas VIII B MTs Darul Ulum Sukaraja) - Alfath Djati S; Ikrima Mailani; A Mualif (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
This research is motivated by the author's findings on several phenomena in Arabic learning at Madrasah Tsanawiyah Darul Ulum Sukaraja, such as the low attention of students in participating in Arabic learning activities, and wanting to know the effectiveness of learning. Therefore, the author feels interested and necessary to conduct this research. The author wants to see the effectiveness of learning Arabic learning on students' mastery of Al Qur'an Hadits subjects at Madrasah in this study, the author uses an observation instrument with an EKOP model evaluation tool (Quality Evaluation and Learning Output). The research subjects were taken from students of class VIII B MTs Darul Ulum for the 2020/2021 academic year, totaling 34 students. Based on the analysis data from the results of the assessment above, it can be conclude that in general Arabic learning at Madrasah Tsanawiyah Darul Ulum Sukaraja takes place effectively, but there appear to be several components of the quality of learning that need to be improved, although on average it meets the requirements to be included in the good classification, but the final score shows the average score = 3.58 is still at the minimum limit of the good classification.